THE EXPERIMENTATION OF PROJECT BASED LEARNING BASED-ECO-CAMPUS TOWARD THE STUDENTS’ PROBLEM SOLVING SKILLS ANDTHE EMOTIONAL ENVIRONMENTAL CLIMATE - Suhendar, Suhendar (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2017)
AbstractThe purposes of this research were to improve the students’ problem-solving skills, and classroom emotional environment climate using project based learning models on the environmental issues material. Subjects in this study were students of S-1 Biology Education Department in University of Muhammadiyah Sukabumi. The method used in this study is a quasi-experiment with two sample classes and using pre-test post-test control group design. Data were collected by using a task of problem-solving skills, emotional environment classroom climate’s questionnaire and interview guides. Implementation of the study began with a pretest continued with learning activity and ended with posttest. The results showed that problem-solving skills and emotional environment classroom climate have improved both in the experimental classroom and in the comparator classroom. The significance test results by using a Mann Whitney non-parametric test showed that problem-solving skills and emotional environment classroom climate in the experimental class were differ significantly with the comparator classroom. Students responded positively to the model of project-based learning. Keywords: Project Based Learning, Problem-Solving Skills, Classroom Emotional EnvironmentalClimate, Environmental Issues Material